Robo4 contributes to the turnover of Peyer’s patch B cells - Fair-Mäkelä Ruth; Ugur Milas; Iftakhar-E-Khuda Imtiaz; Kähäri Laura; Kukkonen-Macchi Anu; Brenyah Heini-Maria; Elima Kati; Miyasaka Masayuki; Pabst Oliver; Jalkanen Sirpa (Springer Nature, 2022)
All leukocytes can get entrance into the draining lymph nodes via the afferent lymphatics but only lymphoid cells can leave the nodes. The molecular mechanisms behind this phenomenon have remained unknown. We employed genome wide microarray analyses of the subcapsular sinus and lymphatic sinus (LS) endothelial cells and found Robo4 to be selectively expressed on LS lymphatics. Further analyses showed high Robo4 expression in lymphatic vessels of Peyer’s patches, which only have efferent lymphatic vessels. In functional assays, Robo4-deficient animals showed accumulation of naïve  B cells (CD19+/CD62Lhi/CD44lo) in Peyer’s patches, whereas no difference was seen within other lymphocyte subtypes. Short-term lymphocyte homing via high endothelial venules to peripheral and mesenteric lymph nodes and Peyer’s patches was also slightly impaired in Robo4 knockout animals. These results show for the first time, selective expression of Robo4 in the efferent arm of the lymphatics and its role in controlling the turnover of a subset of B lymphocytes from Peyer’s patches.